JURIDICAL ANALYSIS OF THE EFFECTIVENESS OF ONLINE SINGLE SUBMISSION (OSS) IMPLEMENTATION RELATED TO LICENSE FOR ENVIRONMENTAL PROTECTION AND MANAGEMENT IN BATAM CITY (RESEARCH STUDY IN BATAM CITY INVESTMENT SERVICE INTEGRATED SERVICES (PTSP) - Indah Wijayanti, Titising; Fadlan, Fadlan; Washliaty, Laily; Siadari Parohha, Lagat (RADJA PUBLIKA, 2023)
The construction of the journal topic above is: